Are the 'rules' for times in set up and duration of red cell transfusion too strict?. Issue 3 (25th April 2016) - Foley, K.; Poles, D.; Mistry, H.; Gray, A.; Bolton‐Maggs, P. H. B.
SUMMARY: Objectives: To discover if any adverse clinical effects have been reported to the UK haemovigilance scheme, Serious Hazards of Transfusion (SHOT) relating to delays in set up of transfusion or extended transfusion time for red cell units. Background: Current guidance for duration of transfusion is based on outdated studies that do not reflect current UK Blood Service practices. Recent evidence suggests that the '30‐min rule' could be extended without adverse effects. Methods: Aggregated data from reports to SHOT covering a 5‐year period (2010–2014) were reviewed in order to identify adverse clinical outcomes related to delay in set up of a red cell transfusion of more than 30 min after removal from cold storage, or total transfusion time of longer than 5 h. Results: Five years of data from SHOT shows that there were no adverse clinical events related to delays in setting up transfusion or extended transfusion time between 2010 and 2014. There were a total of 382 reports which included 143 delays in set‐up, and 239 episodes where transfusion took longer than 5 h. Conclusions: Delays in set up of transfusion and extended transfusion time did not result in any adverse clinical outcomes. Current guidance may be too stringent and lead to increased wastage.